Rare-earth containing magnesium alloys: A review of precipitation behavior and its impact on fatigue performance - Fanjin Yao; Bo Hu; Zixin Li; Jiaxuan Han; Dejiang Li; Qianxi Zhang; Daolun Chen; Xiaoqin Zeng (Journal of Magnesium and Alloys)
Magnesium (Mg) alloys have attracted considerable attention in the automotive and aerospace industries due to their exceptional lightness, high specific strength, and excellent castability. However, their susceptibility to fatigue failure poses significant challenges for the long-term service under cyclic loading. This review systematically explores the precipitation behavior in the representative rare-earth containing magnesium (Mg-RE) alloys and examines the critical role of precipitates in influencing fatigue behavior. The alloying elements and heat treatment play a pivotal role in affecting the precipitation behavior of the Mg-RE alloys. Notably, the β′, β″, and 14H long-period stacking ordered (LPSO) phases serve as primary strengthening precipitates in the Mg-Gd (Y), Mg-Nd, and Mg-RE-Zn based alloys, respectively. The size, quantity, and distribution of these precipitates can be finely controlled through the optimization of aging treatment parameters. Based on the fundamental principles for enhancing fatigue resistance, this review offers a detailed analysis of the effects of precipitates on fatigue behavior, addressing key aspects such as crack initiation, propagation, and fatigue failure under high-cycle fatigue (HCF) conditions. Besides, the effects of precipitates on the cyclic stress response, cyclic deformation characteristics, and fatigue life under low-cycle fatigue (LCF) conditions are systematically summarized. The influence of precipitates on fatigue behavior of Mg-RE alloys is primarily attributed to the mechanisms such as dislocation pinning, crack path deflection, precipitation strengthening, and the suppression of twinning. This review highlights the significance of precipitation behavior in optimizing fatigue resistance and provides valuable insights into future research directions for advancing Mg-RE alloys in the fatigue-critical structural applications.